2019
DOI: 10.1186/s12918-019-0688-9
|View full text |Cite
|
Sign up to set email alerts
|

Urine proteome changes associated with autonomic regulation of heart rate in cosmonauts

Abstract: Background The strategy of adaptation of the human body in microgravity is largely associated with the plasticity of cardiovascular system regulatory mechanisms. During long-term space flights the changes in the stroke volume of the heart are observed, the heart rate decreases, the phase structure of cardiac cycle is readjusted The purpose of this work was to clarify urine proteome changes associated with the initial condition of the heart rate autonomic regulation mechanisms in cosmonauts who hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Activation of proteolysis of cytoskeletal proteins, such as desmin and titin, underlies muscular atrophy, which causes a decrease in the contractile properties of muscles, endurance, and physical performance [2,5]. In addition, changes in the cardiovascular system were detected under the influence of spaceflight factors [6]. An increase in the level of calcium ions and the parathyroid hormone and a decrease in the level of calcitonin were observed on the first day after landing [7].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of proteolysis of cytoskeletal proteins, such as desmin and titin, underlies muscular atrophy, which causes a decrease in the contractile properties of muscles, endurance, and physical performance [2,5]. In addition, changes in the cardiovascular system were detected under the influence of spaceflight factors [6]. An increase in the level of calcium ions and the parathyroid hormone and a decrease in the level of calcitonin were observed on the first day after landing [7].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of the cosmonauts’ urine proteome, we identified various groups of proteins associated with heart rhythm regulation ( Pastushkova et al, 2019 , 2020 ). It was shown that the urine proteome in individuals with the predominance of sympathetic and parasympathetic regulation differed in three proteins: cadherin-13, mucin-1, alpha-1 of collagen subunit type VI, which does not contradict, but complements the results of the blood proteome described above.…”
Section: Discussionmentioning
confidence: 99%
“…Regulatory and metabolic processes in the circulatory system were evaluated on the basis of heart rate variability (HRV) and urine proteomic profile analysis, since HRV indicators reflect the general state of regulatory mechanisms, and the molecular level of heart rate physiological regulation is reflected in the extracellular fluid protein composition studied by proteomics based on mass spectrometry (Pastushkova et al, 2019).…”
Section: Methodsmentioning
confidence: 99%